2019
DOI: 10.5937/aaser1947041m
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the correlation between grain yield and its components in spring barley on an acidic soil

Abstract: A field trial was conducted in 2016-2017 to determine the effect of different rates of mineral fertilisers, especially phosphorus, and lime on grain yield, yield components and their correlation in the spring barley cultivars 'Dunavac' and 'Novosadski 456' under dryland farming conditions at the experimental field of the Secondary School of Agriculture, Kraljevo. The experiment was performed on a very acidic soil (pH H2O 4.5), in a randomised block design with three replications. Grain yield, stem length, numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…A significant association of grain weight per spike with grain number per spike (r=0.644) and 1000-grain weight (r=0.668) was also found. Similar correlations between grain yield and yield components that were observed in present study were also reported by Madić et al (2019), Negash et al (2019) and Aklilu et al (2020).…”
Section: Resultssupporting
confidence: 92%
“…A significant association of grain weight per spike with grain number per spike (r=0.644) and 1000-grain weight (r=0.668) was also found. Similar correlations between grain yield and yield components that were observed in present study were also reported by Madić et al (2019), Negash et al (2019) and Aklilu et al (2020).…”
Section: Resultssupporting
confidence: 92%
“…Topdressing nitrogen fertilizer in study [12] significantly changed chlorophyll content where this practice led to the highest chlorophyll content whereas the minimum one was related to no such application of nitrogen. In barley breeding, physiological studies are mainly focused on correlation between grain yield and its components [23], but we try to assess the relationship between changes in leaf pigment complex and some elements of yield structure.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, knowledge of the relationship between grain yield and its components is of particular practical importance for the implementation of breeding programs 2018;Rohani and Marker, 2016a;Khan et al, 2017;Baye, 2020). The study of yield components is of special importance in stress conditions, as well as in the early generational stages of plant breeding (Dimitrijević et al, 2013;Madić et al 2019). Genotypic and phenotypic correlations provide information on the degree of association of yield components with economic productivity, i.e.…”
Section: Introductionmentioning
confidence: 99%